2012
DOI: 10.3324/haematol.2012.069815
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-10 spot-forming cells as a novel biomarker of chronic graft-versus-host disease

Abstract: ABSTRACTcytokine SFC in patients following HSCT and correlated the results with clinical findings. Furthermore, expression of CD29 (b1 integrin) on monocytes was correlated with plasma levels of fibronectin in patients with active chronic GVHD. Design and Methods PatientsFifty-seven patients who underwent allogeneic HSCT between 1995 and 2009 were included in this study. The patients' demographic data are shown in Table 1. Sixteen patients with chronic GVHD were grouped into mild (n=7), moderate (n=8), and sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 47 publications
2
6
0
Order By: Relevance
“…CD29 expression of monocytes increased after reacting with fibronectin as we have reported 5 . Fibronectin strongly deposited under the basal layer of skin in cutaneous cGVHD 5 10 . Moreover, the expressions of IC IL-10 on intermediate monocytes from patients with active cGVHD stimulated both with and without LPS were significantly higher ( P < 0.05) than those with no or inactive cGVHD ( Fig.…”
Section: To the Editorsupporting
confidence: 75%
See 2 more Smart Citations
“…CD29 expression of monocytes increased after reacting with fibronectin as we have reported 5 . Fibronectin strongly deposited under the basal layer of skin in cutaneous cGVHD 5 10 . Moreover, the expressions of IC IL-10 on intermediate monocytes from patients with active cGVHD stimulated both with and without LPS were significantly higher ( P < 0.05) than those with no or inactive cGVHD ( Fig.…”
Section: To the Editorsupporting
confidence: 75%
“…The expression of CD29 on intermediate monocytes was significantly higher ( P < 0.05) in patients with active cGVHD than those with no or inactive cGVHD. CD29 expression of monocytes increased after reacting with fibronectin as we have reported . Fibronectin strongly deposited under the basal layer of skin in cutaneous cGVHD .…”
supporting
confidence: 80%
See 1 more Smart Citation
“…Macrophages have a bidirectional role in inflammation, and are classified as M1 and M2 macrophages. Increased numbers of infiltrating macrophages in tissue has been observed in refractory aGvHD[ 26 ] and cGvHD[ 27 , 28 ] patients. However, it remains unclear whether macrophages promote or inhibit cGvHD.…”
Section: Discussionmentioning
confidence: 99%
“…or 20 mg/m 2 orally days 1–3, cyclophosphamide 150 mg/m 2 i.v ./orally days 1–3, rituximab standard CLL dose, repeated every 28 days) used by the Czech CLL Study Group reported very good efficacy in elderly/comorbid CLL patients in treatment of first-line ( n = 102; ORR: 79%; median PFS: 20 months) as well as relapsed/refractory disease ( n = 97; ORR: 64%; median PFS: 15 months). Toxicity was acceptable (severe neutropenia, 57 and 49%; severe infections, 14 and 18% of patients) [ 45 ].…”
Section: First-line Treatmentmentioning
confidence: 99%